Human apolipoprotein E isoforms differentially affect bone mass and turnover in vivo1. (15th January 2013) - Dieckmann, Marco; Beil, F Timo; Mueller, Brigitte; Bartelt, Alexander; Marshall, Robert P; Koehne, Till; Amling, Michael; Ruether, Wolfgang; Cooper, Jackie A; Humphries, Steve E; Herz, Joachim; Niemeier, Andreas
Abstract: The primary role of apolipoprotein E (apoE) is to mediate the cellular uptake of lipoproteins. However, a new role for apoE as a regulator of bone metabolism in mice has recently been established. In contrast to mice, the human APOE gene is characterized by three common isoforms APOE ε2, ε3, and ε4 that result in different metabolic properties of the apoE isoforms, but it remains controversial whether the APOE polymorphism influences bone traits in humans. To clarify this, we investigated bone phenotypes of apoE knock‐in (k.i.) mice, which express one human isoform each (apoE2 k.i., apoE3 k.i., apoE4 k.i.) in place of the mouse apoE. Analysis of 12‐week‐old female k.i. mice revealed increased levels of biochemical bone formation and resorption markers in apoE2 k.i. animals as compared to apoE3 k.i. and apoE4 k.i., with a reduced osteoprotegerin (OPG)/receptor activator of NF‐κB ligand (RANKL) ratio in apoE2 k.i., indicating increased turnover with prevailing resorption in apoE2 k.i. Accordingly, histomorphometric and micro–computed tomography (µCT) analyses demonstrated significantly lower trabecular bone mass in apoE2 than in apoE3 and apoE4 k.i. animals, which was reflected by a significant reduction of lumbar vertebrae maximum force resistance. Unlike trabecular bone, femoral cortical thickness, and stability was not differentially affected by the apoE isoforms. To extend these observations to the human situation, plasma from middle‐aged healthy men homozygous for ε2/ε2, ε3/ε3, and ε4/ε4 ( n = 21, n = 80, n = 55, respectively) was analyzed with regard to bone turnover markers. In analogy to apoE2 k.i. mice, a lower OPG/RANKL ratio was observed in the serum of ε2/ε2 carriers as compared to ε3/ε3 and ε4/ε4 individuals ( p = 0.02 for ε2/ε2 versus ε4/ε4). In conclusion, the current data strongly underline the general importance of apoE as a regulator of bone metabolism and identifies the APOE ε2 allele as a potential genetic risk factor for low trabecular bone mass and vertebral fractures in humans. © 2013 American Society for Bone and Mineral Research